Korelasi Intensitas Penggunaan Media Sosial dengan Prestasi Belajar Siswa SDN 1 Dersalam - Siti Robi’ah Nailal Muna; Enjelina Zahwa Artha Mevia; Vina Cahya Maulida; Fina Fakhriyah; Erik Aditia Ismaya (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the correlation between the intensity of social media use and elementary school students' learning achievement. The background of the study is based on the phenomenon of increasing screen time among students due to easy access to social media, which is often more interesting than learning activities. This study uses a quantitative approach with a correlational method and involves 30 fifth grade students of SD Negeri 1 Dersalam who were selected through a purposive sampling technique. Data were collected through a closed questionnaire and analyzed using the Kolmogorov–Smirnov normality test and the Pearson Product Moment correlation test. The results of the study showed a very strong and significant negative relationship between the intensity of social media use and learning achievement (r = -0.968; p <0.05). This means that the higher the duration of social media use, the lower the student's learning achievement. However, some students also use social media as a learning tool, such as accessing educational videos and discussing lessons. This study emphasizes the importance of the role of parents and teachers in supervising and guiding the use of social media so that it becomes a tool that supports learning. These findings are expected to be a reference in developing a balanced digital literacy strategy for students.